Structural identification of pyridinopyrone compounds with anti-neuroinflammatory activity from streptomyces sulphureus DSM 40104 - Hu, Juan; Wang, Zi-Xuan; Li, Pei-Meng; Qian, Pei-Yuan; Liu, Ling-Li (Frontiers in Microbiology, 2023)
This study investigated the chemical composition and biosynthesis pathway of compounds produced by Streptomyces sulphureus DSM 40104. With the guild of molecular networking analysis, we isolated and identified six uncommon structural characteristics of compounds, including four newly discovered pyridinopyrones. Based on genomic analysis, we proposed a possible hybrid NRPS-PKS biosynthesis pathway for pyridinopyrones. Notably, this pathway starts with the use of nicotinic acid as the starting unit, which is a unique feature. Compounds 1-3 exhibited moderate anti-neuroinflammatory activity against LPS-induced BV-2 cell inflammation. Our study demonstrates the diversity of polyene pyrone compounds regarding their chemical structure and bioactivity while providing new insights into their biosynthesis pathway. These findings may lead to the development of new treatments for inflammation-related diseases.